På vei til å bli skrivelærer Lærerstudenten i dialog med teori og praksis - Dons, Carl Fredrik (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2016)
This book focuses on how student teachers for primary and lower secondary school develop competence as teachers of writing. Analyses are based on written, digital dialogues between student teachers, mentors and lecturers during field practice. The dialogues can be characterized as discussions, and are results of SKRIVUT, an intervention study. Using writing as a mediating tool, the goal of SKRIVUT was to facilitate and strengthen the interplay between the two arenas of learning in teacher education.